Allometric analysis sheds light on the systematics and ontogeny of anurognathid pterosaurs. Issue 5 (30th March 2022) - Yang, Zixiao; Benton, Michael J.; Hone, David W. E.; Xu, Xing; McNamara, Maria E.; Jiang, Baoyu
ABSTRACT: Anurognathids are a clade of non-pterodactyloid pterosaurs with generally conservative morphology, but specializations as insectivores. They are represented by a disparate collection of adult and juvenile specimens that range in wingspan from ∼0.24–1 m. There have been concerns about the extent to which ontogenetic variation might affect phylogenetic inference, and indeed how aspects of their ontogeny might relate to the distinctive anurognathid adult morphology. Here we perform allometric analysis on 23 key skeletal dimensions in 13 anurognathid specimens. Our results show that all anurognathids share a common growth trajectory in most dimensions, and that ontogeny affects variation in a minority of characters commonly used in phylogenetic analysis. Excluding these ontogeny-related characters, a new taxon, Cascocauda rong gen. et sp. nov., is established. Based on the ontogenetically corrected dataset, our phylogenetic analysis supports Anurognathidae as the sister-group of Breviquartossa and reveals a general trend of tail reduction in the clade. Allometric growth suggests the anurognathid lifestyle remained consistent throughout ontogeny, maintaining a highly maneuverable flight style by near-isometric development in the wing, small prey (i.e., insects), by strong negative allometry in the skull, and an arboreal habit by strong positive allometry in the claws. This specialized lifestyle suggests retention of plesiomorphic juvenile traits into later ontogeny and facilitated morphological stasis by stabilizing selection during over 40 million years of evolution in the group.